MAGNETITE-ILMENITE-SPINEL INTERGROWTHS IN AMPHIBOLE GABBRO OF THE SEREBRYANSKY KAMEN INTRUSION, CENTRAL URALS - A.V. Kozlov; V.V. Mikhaylov; S.Yu. Stepanov; V.V. Shilovskikh; N.S. Vlasenko (Минералогия)
Ontogenic analysis of magnetite-ilmenite-spinel intergrowths of ore-bearing amphibole gabbro of the Serebryansky Kamen intrusion (Central Urals) and their relationships with rock-forming silicates, apatite and Cu sulfides allowed us to reveal a number of features indicating their nearly synchronous formation. Morphological features of minerals of ore-bearing amphibole gabbro suggest their possible crystallization from silicate, iron oxide and sulfide melts under close-to-eutectic conditions. It is found that regularly oriented ilmenite lamellas in magnetite, which are typically interpreted as exsolution structures, often intersect the boundaries of variously oriented magnetite grains, which is inconsistent with traditional interpretation of their origin. The ontogenetic features of minerals should be taken into account in petrological reconstructions.